# Find the value of:$(i)$. $(-4)\div\frac{2}{3}$$(ii). -\frac{3}{5}\div2$$(iii)$. $-\frac{4}{5}\div(-3)$$(iv). -\frac{1}{8}\div\frac{3}{4}$$(v)$. $-\frac{2}{13}\div\frac{1}{7}$$(vi). -\frac{7}{12}\div(-\frac{2}{13})$$(vii)$. $\frac{3}{13}\div(-\frac{4}{65})$

Given: $(i)$. $(-4)\div\frac{2}{3}$

$(ii)$. $-\frac{3}{5}\div2$

$(iii)$. $-\frac{4}{5}\div(-3)$

$(iv)$. $-\frac{1}{8}\div\frac{3}{4}$

$(v)$. $-\frac{2}{13}\div\frac{1}{7}$

$(vi)$. $-\frac{7}{12}\div(-\frac{2}{13})$

$(vii)$. $\frac{3}{13}\div(-\frac{4}{65})$

To do: To find the value of the given expressions.

Solution:

$(i)$. $(-4)\div\frac{2}{3}$

$=-4\times\frac{3}{2} = -6$

$(ii)$. $-\frac{3}{5}\div2$

$=-\frac{3}{5}\times\frac{1}{2}$

$=-\frac{3}{10}$

$​(iii)$. $-\frac{4}{5}\div(-3)$

$=-\frac{4}{5}\times \frac{1}{-3}$

$=\frac{4}{15}$

$(iv)$. $-\frac{1}{8}\div\frac{3}{4}$

$=-\frac{1}{8}\times\frac{4}{3}$

$=-\frac{1}{6}$

$(v)$. $-\frac{2}{13}\div\frac{1}{7}$

$=-\frac{2}{13}\times\frac{7}{1}$

$=-\frac{14}{13}$

$=-\frac{14}{13}$

$(vi)$. $-\frac{7}{12}\div(-\frac{2}{13})$

$=-\frac{7}{12}\times \frac{13}{-2}$

$=\frac{91}{24}$

$=3\frac{19}{24}$

$(vii)$. $\frac{3}{13}\div(-\frac{4}{65})$

$=\frac{3}{13}\times(-\frac{65}{4})$

$=\frac{15}{-4}$

$=-3\frac{3}{4}$

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

21 Views